2014
DOI: 10.4103/2249-4863.148130
|View full text |Cite
|
Sign up to set email alerts
|

Role of ultrasound with color doppler in acute scrotum management

Abstract: Background and Objective:An acute scrotum is defined as acute pain with or without scrotal swelling, may be accompanied by local signs or general symptoms. Acute scrotal pain is a medical emergency. Depending on cause, the management is entirely different. Torsion of testis and strangulated hernia are surgical emergency; whereas, epididymo-orchitis is treated by medicines. Testicular trauma and obstructed hernia can be differentiated by taking history from patient. Physical examination adds only a little infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The sensitivity found in this study of 78.8% is in line with that reported in other studies while the specificity we found of 98.1% is a little higher than previously reported. 1,[7][8][9] While our means of calculating the sensitivity and specificity were suboptimal (as discussed further below), it is notable that ultrasound was both more sensitive and more specific for epididymo-orchitis than UA. Given that ultrasound is the primary means of diagnosing all sorts of other scrotal pathology (testicular torsion, testicular tumors, hydroceles, etc.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity found in this study of 78.8% is in line with that reported in other studies while the specificity we found of 98.1% is a little higher than previously reported. 1,[7][8][9] While our means of calculating the sensitivity and specificity were suboptimal (as discussed further below), it is notable that ultrasound was both more sensitive and more specific for epididymo-orchitis than UA. Given that ultrasound is the primary means of diagnosing all sorts of other scrotal pathology (testicular torsion, testicular tumors, hydroceles, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is the diagnostic test of choice to evaluate acute scrotal pain. 1 In fact, the company that employs the emergency medicine physicians at the involved institution for this study mandates that its providers order a testicular ultrasound or consult a urologist on any patient with testicular pain. In addition to ultrasound, many experts [2][3][4] recommend a urinalysis (UA) as a routine diagnostic test for patients with scrotal pain primarily because of its purported ability to help diagnose and possibly treat epididymitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DUS compatible with TT reveals severe reduction or absence of testicular blood flow and signs of a twisted spermatic cord. Negative and Positive predictive values for evaluation of TT have been reported to be as high as 100% 11 . However, ultrasound is associated with high inter-examiner variability.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…In selected cases, in which TT is highy suspected, surgical exploration may be indicated without imaging studies, especially if the study will delay surgical exploration. Although scrotal scintigraphy and other tests have been used in the past, Doppler Ultrasonography of the Scrotum (DUS) is the most timely efficient exam available to date, with very good sensitivity and specificity 3 . In this review, we will outline key aspects in diagnostic work-up, specific features and treatment choices of the main conditions that may present as AS.…”
Section: Introductionmentioning
confidence: 99%